Neutralizing monoclonal antibodies improve biodistribution of intravenously administered oncolytic adenovirus in human CD46-transgenic mice. - Masahisa Hemmi; Midori Yamashita; Yoshiko Shimizu; Shinsuke Nakao (PLoS ONE)
Oncolytic viruses are a unique modality with multifaceted mechanisms of action for killing cancer cells and have been developed as a promising therapeutic approach in cancer treatment. The first-in-class agent, talimogene laherparepvec (T-VEC), has shown clinical benefit in patients with advanced melanoma. However, intratumoral administration of oncolytic viruses has several limitations which prevent use against a broader range of cancer types. Here, we propose a novel treatment strategy consisting of the intravenous administration of a genetically engineered oncolytic adenovirus type 11 (Ad11) mixed with anti-Ad11 neutralizing monoclonal antibodies. Ad11, which has minimum binding affinity to human erythrocytes, was modified to selectively replicate in cancer cells. New anti-Ad11 antibody clones were generated which inhibit binding between Ad11 fibers and their natural receptor, CD46. The neutralizing antibodies suppressed viral accumulation in the lungs by about 10-fold in human CD46-transgenic mice without loss of infectivity to cancer cells. Our findings are important in ensuring safe and efficient virus delivery following intravenous administration in humans and may expand treatment options.